(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2015)
The E-commerce service has opened a window for such kindof people. Now, there is no need to go to market and they can purchase thingsonline without any hesitation. It is noticed that the tendency of some of thecompulsive buyers to purchase things even they don’t need it so urgently, hasincreased a little bit because e-commerce has removed the hesitation barrierfor the compulsive buyer. The research revealed that some external and situationalfactors like point-of-purchase displays are also responsible for non-compulsivebuying. While, internal core factors like emotional instability, anxieties areresponsible for compulsive buying.